Factors affecting willingness to receive a kidney transplant among hemodialysis patients in West China: A cross-sectional survey. Issue 18 (May 2017) - Tan, Qiling; Song, Turun; Jiang, Yamei; Qiu, Yang; Liu, Jingpeng; Huang, Zhongli; Wang, Xianding; Lin, Tao
Abstract : Abstract: Many factors are associated with the willingness of ESRD patients to receive a kidney transplant. No data are available for patients in China. The study aim was to describe the attitudes toward transplantation in a cohort of patients at a single dialysis center in China. A study questionnaire derived from previously published literature was completed by 239 hemodialysis outpatients. Factors associated with willingness to receive a transplant were identified by univariate and multivariate logistic regression analyses. The respondents were primarily men 50.7 ± 15.1 years of age; 46.4% were willing to receive a transplant. Younger age (OR = 0.928, 95% CI: 0.898–0.959), good self-reported health (OR = 0.203, 95% CI: 0.081–0.51), and awareness of the benefits of transplantation (OR = 0.195, 95% CI: 0.083–0.456) were less likely to deny the transplant. Patients ⩽60 years of age were about 13 times more likely to favor transplantation than those >60 years of age (OR = 12.99, 95% CI: 3.75–45.45). For every 10 years under 60, participants were 2.16 times more willing to receive a kidney transplant (OR = 2.16, 95% CI: 1.53–3.02). Older patients were also less likely to be referred for evaluation (OR = 0.955, 95% CI: 0.923–0.989, P = .009). The percentage of ESRD patients in China, particularly older patients, who are willing to accept a transplant, is relatively low. A better understanding of the benefits of transplantation is needed to increase their acceptance.